Drill statt Beratung ? - Zum Aufstieg und Fall des Training & Visit-Systems im landwirtschaftlichen Beratungsdienst Westafrikas - Dirk Kohnert (Entwicklung und ländlicher Raum, 1990)
– The training and visit (T & V) agricultural extension system has been adopted in West Africa to improve the transfer of technology to farmers with the ultimate aim of increasing agricultural production. The West African experience is discussed in this article, showing that the T & V messages to increase staple food production have not been adopted by the small farmers because the innovations were elaborated by agricultural research stations without due consideration to the particular constraints of the different production systems and target groups. Recent evaluations of different agricultural projects revealed the lack of adequate methods to develop innovations as a major bottleneck. Therefore, and in order to reduce the high cost of extension staff, it is argued that the latter should concentrate on the extension of methods to promote participatory technology development on demand of individual peasant innovators within each of the target groups. It is suggested that the diffusion of innovations should be left to more efficient channels of communication, such as local radio service, newsletters or professional private organizations. – – Le système de vulgarisation agricole pour la formation et la visite (Training and Visit, T &V) a été adopté en Afrique de l'Ouest pour améliorer le transfert de technologie aux agriculteurs dans le but ultime d'accroître la production agricole. L'expérience ouest-africaine est discutée dans cet article, montrant que les messages T & V pour augmenter la production alimentaire de base n'ont pas été adoptés par les petits agriculteurs car les innovations ont été élaborées par les stations de recherche agricole sans tenir compte des contraintes particulières des différents systèmes de production et des groupes cibles. Les évaluations récentes de différents projets agricoles ont révélé comme un goulot d'étranglement majeur le manque de méthodes adéquates pour développer les innovations. Par conséquent, et afin de réduire le coût élevé du personnel de vulgarisation, on fait valoir que ce dernier devrait se concentrer sur l'extension des méthodes de promotion des méthodes participatif à la demande des innovateurs paysans individuels dans chacun des groupes cibles. Il est suggéré que la diffusion des innovations soit laissée à des canaux de communication plus efficaces, tels que le service de radio locale, les bulletins d'information ou les organisations professionnelles privées.
Keywords: F35; F54; N47; Z13; 330; Landwirtschaftliche Beratung; Westafrika; Benin; T & V; Training & Visist; Monitoring